Recent Developments in Mechatronics and Intelligent Robotics Proceedings of the International Conference on Mechatronics and Intelligent Robotics (ICMIR2017) - Volume 1 (Advances in Intelligent Systems and Computing,, 2018)
This book gathers the Proceedings of the International Conference on Mechatronics and Intelligent Robotics (ICMIR2017), held in Kunming, China, on May 20-21, 2017. The book covers a total of 172 papers, which have been divided into seven different sections: Intelligent Systems, Intelligent Sensors & Actuators, Robotics, Mechatronics, Modeling & Simulation, Automation & Control, and Robot Vision. ICMIR2017 provided a vital forum for discussing the latest and most innovative ideas from both the industrial and academic worlds, and for sharing best practices in the fields of mechanical engineering, mechatronics, automatic control, electrical engineering, finite element analysis and computational engineering. The main focus of the conference was on promoting interaction between academia and industry, allowing the free exchange of ideas and challenges faced by these two key stakeholders and encouraging future collaboration between the members of these groups. The proceedings cover new findings in the following areas of research and will offer readers valuable insights: Mechatronics Intelligent mechatronics, robotics and biomimetics; Novel and unconventional mechatronic systems; Modeling and control of mechatronics systems; Elements, structures and mechanisms of micro and nano systems; Sensors, wireless sensor networks and multi-sensor data fusion; Biomedical and rehabilitation engineering, prosthetics and artificial organs; Artificial Intelligence (AI), neural networks and fuzzy logic in mechatronics and robotics; Industrial automation, process control and networked control systems; Telerobotics, Human-Computer Interaction; and Human-Robot Interaction. Robotics Artificial Intelligence; Bio-inspired robotics; Control algorithms and control systems; Design theories and principles; Evolutional r obotics; Field robotics; Force sensors, accelerometers, and other measuring devices; Healthcare robotics; Human-Robot Interaction; Kinematics and dynamics analysis; Manufacturing robotics; Mathematical and computational methodologies in robotics; Medical robotics; Parallel robots and manipulators; Robotic cognition and emotion; Robotic perception and decisions; Sensor integration, fusion, and perception; and Social robotics.